New Industry 4.0 Advances in Industrial IoT and Visual Computing for Manufacturing Processes: Volume II - Luis Norberto López de Lacalle; Jorge Posada (Applied Sciences, 2022)
The second volume of the Special Issue New Industry 4 [...]